Multi-disciplinary design of wings for transport aircraft operating at high subsonic speed - Djafri, Demil Y. (Cranfield University, 1995)
In this thesis a methodology for designing wings for transport aircraft operating at high subsonic speed is investigated. Several methods are studied, including more accurate methods such as the computational methods. These are used as an addition to the semi-empirical methods. Several attempts have been made to build a computerised aircraft design in the past. Mos *t of the conceptual aircraft design programs that are available are based on the semi-empirical method only. As faster computers become available, a method for designing a high subsonic aircraft wing is studied by including computational aerodynamic and computational structural analysis in the integration process. SPARV is used as the computational aerodynamic program and NASTRAN is used as the computational structural analysis program. The objectives of this thesis are to study a method of performing, the conceptual design of win_qs for transport aircraft operatin_q at high subsonic speed and to demonstrate that aerodynamics analysis using, Computational Fluid Dynamics (CFD) and structures analysis using the Finite Element Method (FEM), can be coupled with the aircraft synthesis program in a seamless distributed computing environment. The achievement of these objectives is demonstrated by, applying the methodology to specific wing design. This method has been validated and tested for transport aircraft operating at high subsonic speed, but application on military transports may also be valid. An example case study is presented in this thesis. Improvement of the method for future development is also considered in the thesis. These include the use of a more powerful computational aerodynamics package.